Using protein turnover assay to explore the drug mechanism of Carfilzomib - Tao Yonghui; Ding Xinyu; Jia Caiwei; Wang Chengcheng; Li Chuanyin (Acta Biochimica et Biophysica Sinica)
Carfilzomib (CFZ) is the second-generation proteasome inhibitor that is approved by Food and Drug Administration (FDA) of USA for the treatment of relapsed and refractory multiple myeloma. Although the preclinical and clinical efficacy of CFZ is obvious, the mechanism by which CFZ leads to cell death has not been fully elucidated. Since CFZ primarily functions as a proteasome inhibitor, profiling CFZ-induced changes in protein turnover at the systematic level is sufficient and necessary. In this study, we characterize the effects of CFZ on the stability of 15,000 human proteins using Protein Turnover Assay (ProTA). CFZ affects fundamental cellular glycolysis, nitric oxide production and proteasome subunit homeostasis in multiple myeloma cells. In addition, LY294002 or KU-0063794 has synergistic effects with CFZ in multiple myeloma treatment. A profound understanding of how cells respond to chemotherapeutic agents provides insights into the basic mechanism of drug function and the rationale for CFZ combination therapy.